Charakter prawny wniosku odwoławczego w procesie karnym (art. 29 § 2 Kodeksu postępowania karnego) - Łukowiak, Bartosz (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The purpose of this work is to analyze the legal nature of demands contained in the appeal, including their function in the criminal trial, as well as to determine whether and to what extent their content is binding on the appellate court, and whether the appellant is entitled to amend them during the appeal proceedings. The article focuses on presenting the views expressed so far in this matter in the literature of polish criminal procedure and jurisprudence of criminal courts. In the next step, the author analyzes the possible impact of the amendment of July 19, 2019, on those views. The article also contains the presentation of how to interpret Article 29 § 2 of the Code of Criminal Procedure in its current wording.